The Mitoni Tradition as Social, Cultural, and Spiritual Reinforcement of Javanese Society - Nana Najmina; Eny Kurdarini (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
This study examines how the social, cultural and spiritual values of the Mitoni tradition has “strengthened” the social and spiritual culture of the Javanese Muslim community. The Mitoni tradition is one of the best preserved tradition of the Javanese people from generation to generation, especially in Central Java. However, this tradition has received a lot of criticism from conservative religious adherents who accuse it of being a deviant practice. Yet this tradition embodies social, cultural and spiritual values that teach people to live together to create social harmony. This research uses a qualitative descriptive approach. It argues that Mitoni tradition contains irreplaceable cultural-historical values. By carrying out the tradition, the community hopes that someday the young generation can live in security and can embody good moral and personal traits that can then strengthen their social and spiritual bonds with fellow human beings. Kajian ini bertujuan untuk mengkaji nilai sosial, kultural dan spiritual tradisi Mitoni sebagai “penguatan” sosial kebudayaan spiritual masyarakat Muslim Jawa. Tradisi Mitoni ini merupakan salah satu adat yang sangat dilestarikan oleh masyarakat Jawa khususnya di Jawa Tengah yang dilakukan secara turun-temurun. Hanya saja, tradisi ini banyak mendapatkan kritikan dari aliran keagamaan konservatif yang menuduh sebagai tradisi menyimpang dari ajaran Islam. Padahal semestinya, tradisi mengandung nilai sosial, kultur dan spiritual dalam tradisi ini yang mengajarkan masyarakat untuk hidup bersama untuk menciptakan harmoni sosial. Penelitiaan ini menggunakan kualitatif dengan pendekatan deskriptif. Maka hasil kajian ini bahwa tradisi Mitoni mengandung banyak nilai-nilai historis dan kultural. Dengan melaksanakan tradisi mitoni masyarakat berharap kelak anak yang akan lahir diberi keselamatan dan dapat menjadi anak yang memiliki kepribadian yang baik serta dapat menjadi suri tauladan, selain itu dengan mengadakan tradisi tersebut secara tidak langsung mereka sudah mempererat tali silaturrahmi antar sesama.